YouTube as a resource: How effective is it for tafsir and Quranic sciences - Nadeem Beg, Mirza Arshad (Journal of Islamic Sciences, 2020)
In this research, I gathered the most important authentic scientific lessons related to the Qur’an and its sciences, with a brief idea showing for each lesson, and my goal of this research is to encourage the use of electronic tools in teaching interpretation and the sciences of the Qur’an, And collecting electronic scientific materials in them for the specialists in that after it was separated in several channels. In this research, I followed the method of conclusion in organizing information about how to benefit from YouTube, and the induction tracking method to collect clips that are in the thousands and contain lessons in the principles of interpretation and Quranic sciences, and through this research reached the YouTube has filled scientific benefits, especially Quran and its Sciences can take advantage of those who wanted to expand on his knowledge, no doubt that electronic lessons through electronic platforms have negatives so it is not equivalent presence traditional classes.